The Association Between Body Mass Index (BMI) and Age of Menarche in Adolescents - Ulfa Diya Atiqa; Andi Hardianti; Nurul Muchlisa (Ilmu Bersama Center, 2026)
Adolescence is a critical transitional period characterized by rapid physical and reproductive maturation. One of the primary indicators of female pubertal development is menarche, the first menstrual period, which reflects the functional maturation of the reproductive system. In recent decades, the age at menarche has shown a declining trend globally, potentially influenced by changes in lifestyle and nutritional status. Body Mass Index (BMI) is commonly used to assess nutritional status and has been identified as an important determinant of pubertal timing. This study aimed to systematically analyze the relationship between BMI and age at menarche through a systematic review approach. A literature search was conducted in two databases, Google Scholar and PubMed, identifying a total of 2,198 articles published between 2020 and 2024, selected using PRISMA guidelines. After screening and eligibility assessment, 11 articles met the inclusion criteria and were included in the final analysis. The findings consistently demonstrate a statistically significant association between higher BMI and earlier menarche (p<0.05). Early menarche is associated with long-term health risk, including cardiovascular disease, metabolic disorders, and certain cancers. BMI plays a significant role in determining the timing of menarche. Maintaining optimal nutritional status during adolescence is essential to support balanced reproductive development and long-term health outcomes.